Investigation of microstructure-property relantionships of magnesia-hercynite refractory composites by a refined digital image correlation technique. Issue 13 (October 2019) - Khlifi, Imad; Pop, Octavian; Dupré, Jean-Christophe; Doumalin, Pascal; Huger, Marc
Abstract: Industrial magnesia-spinel bricks destined for thermal shock applications often show more flexibility and improved crack growth resistance. Components from the spinel structure group are usually added to promote microcracking coming from thermal expansion mismatch. This leads to the development of toughening mechanisms that are very effective in improving the crack propagation resistance. Magnesia-hercynite composites were investigated in order to highlight their fracture process, with regard to their microstructure, by using Digital Image Correlation (DIC). The direct measurement of displacement fields between digital images of the reference state and the deformed one has provided valuable information on material deformation during loading. The aim of this work was to investigate the fracture behaviour of refractories through the coupling of the Wedge Splitting Test (WST) and DIC. By using a refined DIC process transformation taking into account a discontinuity of displacement, called 2P-DIC, a more effective characterisation of the fracture behaviour was achieved.